2012
DOI: 10.1186/ar3783
|View full text |Cite
|
Sign up to set email alerts
|

Placebo analgesia: cognitive influences on therapeutic outcome

Abstract: The therapeutic response to a drug treatment is a mixture of direct pharmacological action and placebo effect. Therefore, harnessing the positive aspects of the placebo effect and reducing the negative ones could potentially benefit the patient. This article is aimed at providing an overview for clinicians of the importance of contextual psychosocial variables in determining treatment response, and the specific focus is on determinants of the placebo response. A better understanding of the physiological, psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In our empirical clinical study, we tested just the outcome of the placebo effect that showed response attenuation in a variety of brain structures related to pain perception. Relevantly, placebo-related changes involved the dorsal lateral prefrontal cortex, which is one of the key areas mediating the top-down effects of placebo 40,41,42,43,44 . Compared with placebo, naproxen showed a stronger effect on core regions of the pain-processing system.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…In our empirical clinical study, we tested just the outcome of the placebo effect that showed response attenuation in a variety of brain structures related to pain perception. Relevantly, placebo-related changes involved the dorsal lateral prefrontal cortex, which is one of the key areas mediating the top-down effects of placebo 40,41,42,43,44 . Compared with placebo, naproxen showed a stronger effect on core regions of the pain-processing system.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…Few specific imaging studies have been done in patients with chronic OA, even though the placebo effect is notable in this clinical condition 38,39 . Experimental work has shown that placebo analgesia is mediated by the activation of descending, mostly opioids, pain modulatory circuits with the implication of the prefrontal cortex, anterior cingulate cortex, and deep elements like the PAG and amygdala 40,41,42,43,44 . As a result, the brain response to nociceptive stimulation is attenuated 3,45 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…For example, placebo analgesia, thought to be mediated by conscious or unconscious (e.g . conditioned) expectations (Watson et al, ), is opioid‐mediated (Benedetti et al, ). Furthermore, behavioural and neuroimaging studies show that the analgesic effect of synthetic opiates during experimental pain is blocked by negative suggestion (Bingel et al, ).…”
Section: Opioid Function In Pain Vulnerability and Resiliencementioning
confidence: 99%
“…As the current study was parallel in design, it is less likely that Hawthorne, placebo effect or therapeutic relationship influenced the data. The placebo response is a biologically active process known to reduce pain and often encouraged in clinical practice (Watson et al, 2012). However, it may confound the mechanism of action of therapies when studies do not compare two active modalities in a parallel fashion.…”
Section: Discussionmentioning
confidence: 99%